Assessing the bioaccumulation of copper and zinc using bird as bioindicator in different wetland ecosystems of Odisha, India - Bibhu Prasad Panda; Radha Kumari; Abanti Pradhan; Bishal Kumar Majhi; Pratik Acharya; Siba Prasad Parida (Environmental Systems Research)
Abstract The developing countries have been intensified by urbanization and anthropogenic activities releasing heavy metals into the environment leading to various environmental challenges. This study evaluates Cu and Zn pollution in wetland ecosystems across eight locations in Odisha, India. It utilizes Cattle egret’s feathers and describes these birds as bioindicators to assess the bioaccumulation of these metals. Soil, prey (invertebrates and fish) and feathers were sampled from different sampling locations to measure metal concentrations using Atomic Absorption Spectroscopy. Findings have revealed spatial variations, with the highest Cu levels observed in Bhadrak soil (34.27 µg/g), Koraput prey (9.27 µg/g), and Koraput feathers (15.62 µg/g) and lowest in Chandaneswar soil and prey (13.43 µg/g and 2.88 µg/g), in Hirakud Feather (8.39 µg/g). The highest Zn levels were recorded in Koraput soil (55.45 µg/g), Koraput prey (49.94 µg/g), and Koraput feathers (84.05 µg/g) and lowest in Talcher soil (29.71 µg/g), Bhadrak prey (19.61 µg/g) and in Hirakud prey (38.9 µg/g) respectively. Positive correlations were recorded for Cu as well as Zn concentrations among soil, prey and feather samples of different locations which represents the bioaccumulation pattern of heavy metals in the wetland ecosystem and moving up through the trophic levels to the higher organisms, especially to the birds. This can be a contributing factor to the declining population of many wetland dependent birds as well as a threat to the health of other animals and humans that depend on these ecosystems. Clinical trial registration: Not applicable. Graphical Abstract